Research among Forced Migrants in Poland from the Methodological Point of View and Ethical Perspectives (London Journal of Research In Humanities and Social Sciences, 2023)
The aim of the article is to identify ethical tensions between the cognitive function of science, humanitarian reasons for undertaking research work and its practical goals in research conducted among forced migrants. Differences between researchers and respondents in the dimensions of social, economic and political status determine the challenges of building ethical relationships, not only as meeting the imperative of & quot; do no harm & quot; by ensuring the safety of the subjects and protecting them from abuse. In a team composed of researchers with an external and internal status towards the studied group, we consider the possibilities of equalizing asymmetrical relationships, creating relationships based on mutual benefits and the involvement of respondents in the research process. The source of reflection is the analysis of research reports and the experience of own research work carried out among forced migrants by co-authors of this text.